Industry relatedness, FDI liberalization and the indigenous innovation process in China. Issue 2 (1st February 2020) - Howell, Anthony
ABSTRACT: This paper employs a structural innovation model to study the process of indigenous innovation in China and the role of industry relatedness. To better take into account China's transitioning economy context, it further tests to what extent the relationship between relatedness and firms' innovation process is influenced by the relaxation of foreign ownership controls, an arguably exogenous shock. Controlling for selection, simultaneity and unobserved heterogeneity, the results show that firm research and development (R&D) boosts innovation output, which in turn enhances firm productivity. Relatedness economies are positively related to each phase of innovation, although the size of the effects depends on the type of firm and the stage of innovation. Foreign direct investment (FDI) liberalization encourages firms to rely more on relatedness economies: (1) to complement R&D spending that is required to adapt foreign technologies to local applications; (2) to recombine knowledge from related industries in order to bring forth new proprietary ideas, processes or concepts; and (3) to help solve process or organizational problems faced in related industries.